Ecocardiografía bidimensional normal en conejos neozelandeses blancos - Chiaramonte, P. (2010)
Authors describe the position of the right and left parasternal, subxifoid and left subcostal echocardiographic windows, the anatomical aspects of the reference echotomograms of the studied windows, and present the obtained mean values of the different echocardiographic accidents and indexes in 38 New Zealand rabbits.\nThe obtained means values were: interventricular septal thickness in systole (IVSTs): 2.95 mm ± 0.53 mm; interventricular septal thickness in diastole (IVSTd): 4.41 mm ± 1.12 mm; left ventricular systolic diameter (LVSD): 15.76 mm ± 1.77 mm; left ventricular diastolic diameter (LVDD): 11.14 mm ± 1.73 mm; left ventricular posterior wall thickness in diastole (LVPWTd): 3.59 mm ± 0.54 mm; left ventricular posterior wall thickness in systole (LVPWTs): 4.53 mm ± 0.71 mm; fractional shortening (FS%): 29.72 % ± 5.79 %; ejection fraction (EF%): 64.09 % ± 8.61 %; aortic diameter (AoD): 8.87 mm ± 1.21 mm; left atrium diameter (LAD): 10.61 mm ± 1.28 mm; left atrium and aortic diameter ratio (LA:AO): 1.21 ± 0.21; E-point septal separation (EPSS): 2.18 mm ± 0,6 mm and mitral annulus excursion (MAE): 5.61 mm ± 0,83 mm.\n